Perlindungan Sensor Suhu Cu/Ni dengan Nitroselulosa (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2024)
Coating of Cu/Ni with nitrocellulose (NC) has been carried out with the aim of determining the effect of using NC as a protective film on the sensitivity and activation energy of the sensor. The samples used were Cu/Ni and Cu/Ni/Cu where the NC coating on Cu/Ni was carried out using a spray method with a pressure of 1.2 Mpa. Both sensor samples were used to measure the temperature of liquid nitrogen (liquid N2) which was varied from -160C - 0C. In addition to temperature, voltage and current were also measured. The sensitivity value was obtained from the slope of the resistance curve against temperature, while the activation energy was obtained from the slope of the logarithm of conductivity against one per absolute temperature. From the sensitivity test, it is known that both sensors have a tendency to be more sensitive when the temperature is lowered, but the presence of the NC layer causes a decrease in sensitivity of up to 18.9%, namely from 3.95 /C to 3.18 /C at a temperature of -160C following the equation S(T)=0.10e-0.012T. The use of NC protective layer can also increase the activation energy by 1.3%, namely from (4.29  0.01)x10-9 eV to (4.35  0.01)x10-9 eV. These results can be used as a consideration for temperature sensor manufacturers that the use of NC protective layer is important but can reduce sensor sensitivity.